The excellence of the Arabs - Ibn Qutaybah, ʻAbd Allāh ibn Muslim, 828-889? (Library of Arabic Literature, 2019)
A spirited defense of Arab identity from a time of political unrestIn ninth-century Abbasid Baghdad, the social prestige attached to claims of Arab identity had begun to decline. In The Excellence of the Arabs, the celebrated litterateur Ibn Qutaybah locks horns with those members of his society who belittled Arabness and vaunted the glories of Persian heritage and culture. Instead, he upholds the status of Arabs and their heritage in the face of criticism and uncertainty.The Excellence of the Arabs is in two parts. In the first, Arab Preeminence, which takes the form of an extended argument for Arab privilege, Ibn Qutaybah accuses his opponents of blasphemous envy. In the second, The Excellence of Arab Learning, he describes the fields of knowledge in which he believed pre-Islamic Arabians excelled, including knowledge of the stars, divination, horse husbandry, and poetry. By incorporating extensive excerpts from the poetic heritage--"the archive of the Arabs"--Ibn Qutaybah aims to demonstrate that poetry is itself sufficient evidence of Arab superiority.Eloquent and forceful, The Excellence of the Arabs addresses a central question at a time of great social flux, at the dawn of classical Muslim civilization: What does it mean to be Arab?